Implementasi Word of Mouth Marketing Brand Ciganjur Outdoor dalam Membangun Brand Awareness - Muhammad Naufal Zundan; Jamiati KN (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
Word of mouth (WOM) marketing is an effective marketing communication strategy that utilizes direct recommendations from consumers to other potential consumers. This research aims to analyze the implementation of the WOM marketing strategy carried out by Ciganjur Outdoor, an MSME providing outdoor equipment rental services in Jakarta. The research was conducted using qualitative methods through in-depth interviews, observation and documentation. The results show that Ciganjur Outdoor has implemented a WOM strategy with the elements talkers, topics, tools, taking part, and tracking. Through direct interaction with potential consumers and utilizing feedback, Ciganjur Outdoor seeks to build brand awareness and strong relationships with consumers. The obstacles faced are the lack of human resources and the lack of optimal use of outdoor communities. This research is expected to provide insight into the implementation of WOM strategies, especially for MSMEs in the service industry.